Research and practice of PON fault intelligent detection and recovery technology - Qi YU; Yanbin SHI; Shipeng QIU (Dianxin kexue)
Based on current situation that PON network faults are mainly processed around the user account password and terminal problems,and all the complex phenomena and network issues involved are sent to the operation and maintenance department,leading to low failure processing efficiency and high treatment pressure,an end-to-end fault diagnosis and repair method was proposed based on the customer resource tree.Through adopting big data analysis technology and service capability opening technology,an end-to-end fault detection system from service platform to client terminals was built and fault phenomena,conclusions and treatment methods of the nodes in the resource tree were combed,and fault processing scenarios were listed to verify the accuracy of fault detection and fast recovery.The result shows that the failure interception efficiency is improved by 34%.